2021
DOI: 10.1039/d0gc04314a
|View full text |Cite
|
Sign up to set email alerts
|

A sustainable solvent based on lactic acid and l-cysteine for the regeneration of keratin from waste wool

Abstract: Keratin dissolution is the first step toward reusing protein-rich biomass such as waste wool, hair, and feather.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…This study [22] established the functionality of lactic acid and L-cysteine utilization in the production of a nontoxic and biodegradable DES that can facilitate significant keratin recovery from wool without compromising the keratin structure [22]. Indeed a previous study has shown that the use of this novel DES has the potential of producing keratin composed of proteins with high molecular masses [22]. In the current study, we are therefore seeking to optimize the recovery of keratin from waste coarse wool using this new DES composed of lactic acid and Lcysteine.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…This study [22] established the functionality of lactic acid and L-cysteine utilization in the production of a nontoxic and biodegradable DES that can facilitate significant keratin recovery from wool without compromising the keratin structure [22]. Indeed a previous study has shown that the use of this novel DES has the potential of producing keratin composed of proteins with high molecular masses [22]. In the current study, we are therefore seeking to optimize the recovery of keratin from waste coarse wool using this new DES composed of lactic acid and Lcysteine.…”
Section: Introductionmentioning
confidence: 87%
“…presence of a peak at around 1040 cm -1 in keratin samples is due to the presence of cysteine-S-sulfonated residues in the recovered keratin [22,40]. Hence, the result showed that keratin regeneration from wool using L-cysteine and lactic acid is a safe method for preserving the protein structure of keratin; however, choosing a proper experimental parameter, particularly dissolution temperature may be considered in large-scale applications.…”
Section: Characterization Of the Obtained Keratinsmentioning
confidence: 96%
See 2 more Smart Citations
“…The intrinsic nature of establishing the H-bond also confers unique properties that apply to the electro-polishing of metals, metal electrodeposition and metal extraction [29]. DESs should be extended to several new biomasses to implement the biorefinery scenario with new solutions and unexplored options for achieving new base chemicals [156].…”
Section: Conclusion: Perspectives and Criticisms On The Use Of Desmentioning
confidence: 99%